Clinical Profile of Dry Eye Disease at the Philippine General Hospital - Ruben Lim Bon Siong, MD; Karlo Marco DR Claudio, MD; Ivo John S Dualan, MD; George Michael N Sosuan, MD (Philippine Journal of Ophthalmology)
Objectives: To describe the population of dry eye disease (DED) patients seen at the Philippine General Hospital (PGH) Dry Eye Clinic, and to compare the diagnosis, type, and severity of DED using Oculus Keratograph® 5M (Oculus GmbH, Wetzlar, Germany) with clinical diagnosis.